The dynamics of fat in the muscle tissue of the artificially reared salmon fry - Kushnir, T.I. (Baltijskij Nauchno-issledovatelskij Institut Rybnogo Khozyajstva; "Zvaigzne", 1970)
The fat content in fish body considerably fluctuates depending on the season, the age of fish, its biological state, the condition of its food supply and other environmental factors. The aim of the investigations was the establishment whether similar changes in the fat dynamics occur in the organism of the salmon (Salmo salar) fry reared in fish hatcheries on the artificial feed, i.e. in the fish fully provided with food during the period of their rearing. The analyses showed that the decrease of the fat content during the period preceding the transition to the smolt stage was stated both for fry in the ponds and for these reared on the artificial feed. It was established that fat, the chief energetic reserve in the animal organism, is indeed spent for the physiological reconstruction of the organism, to prepare it for the life in other environmental conditions. Published Not Known